Grassland Productivity and Ecosystem Services - Lemaire, Gilles (CABI, 2014)
The 'grassland' biome, defined as permanent vegetation of herbaceous plant communities, covers approximately 25% of the terrestrial Earth surface, approximately equivalent to the area of forest lands or the area of cultivated lands. Among the different types of grassland ecosystems, it is important to distinguish: (i) the climatically determined grasslands, in areas where water availability is not enough to allow the development of forest ecosystems and where natural vegetation remains at the herbaceous succession stage in dynamic equilibrium with herbivores (Lauenroth, 1979); and (ii) the anthropogenic grasslands, mainly located within temperate climate regions, where woody vegetation is excluded and herbaceous plant communities are main- tained by means of human management for domestic herbivore production. Among these anthropogenic grasslands it is also possible to distinguish long-term natural- ized grasslands from cultivated grasslands with a wide range of variation in degree of intensification. All these grasslands play an important role in agronomic, economic and social activities in the exploitation of their resources by domestic herbivores for food and fibre production.